Monitoring system of student performance using data warehouse (Case study: INSTITUT TEKNOLOGI SUMATERA) - Ramdani, Ahmad Luky; Hanifah, Raidah; Pilopa, Okta (Institut Teknologi Dirgantara Adisutjipto, 2018)
Improving the quality of learning is one of the things that must be achieved in the college academic process. To achieve this, monitoring and evaluation of the results of the learning process is needed, namely by looking at student performance. Based on this, the research aims to develop a university data warehouse with student performance objects that will be used by the board application for the monitoring process. The application was successfully developed with several main features, namely: a) displaying the number of students based on year, region and the entrance to college, b) displaying a comparison of the number of students in each academic year based on student status , d) display student performance every academic year and e) KPI values based on needs analysis. These features have been tested using the blackbox approach and the test results show that the features work properly and produce outputs in corresponding to the test scenario.